Intravenous fluids for Moderate to Severe nausea and vomiting in pregnancy In the Community (IMSIC): Implementation protocol. (September 2022) - Canty, Ms Alison; Alexandrou, Evan; Dickson, Hugh; Lawson, Kenny; Schmeid, Virginia; van Vorst, Mr Daniel; West, Ms Dana; Makris, Angela
Abstract : Introduction: After reviewing emergency department presentations for hyperemesis gravidarum (HG) and mapping services available to women with HG across one local health district, significant gaps were identified. To address this gap a protocol was developed in consultation with clinicians, researchers and a consumer representative. We aim to examine the effectiveness, feasibility, implementation and dissemination of intravenous hydration for the treatment of moderate to severe HG in women's homes via a hospital in the home (HITH) model. Methods: A before and after hybrid implementation design has been chosen. Women presenting to an emergency department (ED) will be approached to participate. Inclusion criteria: are women with a confirmed viable pregnancy, 16 years of age or older, with a pregnancy unique quantified emesis (PUQE) score of seven or more, who are willing and able to receive intravenous treatment (IVT) in their home. Women participating will receive IVT over three days at home. Quality of life tools and a satisfaction survey will be undertaken. Women who require ongoing management of their HG past the initial three days can continue in this model of care. This project is ethics approved. The outcomes of interest include rates of representation to ED. Acceptability, feasibility and sustainability will be assessed using semi structured interviews of clinicians and managers from services providing care to women with HG and with women who receive treatment. Economic analysis and implementation cost will be undertaken. Results: Analysis of before and after intervention data will be undertaken with pre and post-test survey data being described using descriptive and inferential statistics. Qualitative interviews will be analysed using thematic analysis. Conclusion: It is anticipated that the results from the evaluation of IMSIC will demonstrate improved health outcomes for women with moderate to severe HG and that the findings will inform implementation on a larger scale.